SOCIAL BRAND MANAGEMENT IN A POST COVID-19 ERA. - Dias, Patricia; Duarte, Alexandre ([S.l.] : ROUTLEDGE, 2023)
As activity significantly reduced during mandatory lockdown periods aiming to contain the spread of Covid-19, the relationship between organizations and their stakeholders became almost strictly digital. While some brands already have developed digital channels and made a smooth transition, others struggled to remain connected to their consumers and in the process created a panoply of new digital strategies and practices. This book discusses how the Covid-19 pandemic changed the way consumers relate with brands and how brands can reinvent, improve, or optimize themselves to meet new needs, expectations, and preferences of consumers. Drawing on empirical data about how consumers are connecting with brands in a Covid-19 recovery period, this book suggests becoming a social brand as a strategy for coping with changes in consumer behaviour. A social brand has two main dimensions: it is sociable (active on social media, humanized, and empathic) and it is socially committed (transparent and sustainable). In this concise book, the authors examine case studies of brands that coped successfully with Covid-19 and positioned themselves strongly in this post-pandemic retake period to suggest good practices. It offers an informed discussion on how brands can adapt to changes in consumer behaviour and build stronger connections with consumers. Social Brand Management in a Post Covid-19 Era provides an accessible yet comprehensive overview of brand management in a post-pandemic environment that will be of interest to marketing and communication academics, researchers, and students.
Keywords: Product management; Branding (Marketing); COVID-19 Pandemic, 2020- -- Influence; BUSINESS & ECONOMICS / General; BUSINESS & ECONOMICS / Consumer Behavior; BUSINESS & ECONOMICS / Marketing / General